Culture of Abuse of Power Due to Conflict of Interest to Corruption for Too Long on The Management form Resources of Oil and Gas in Indonesia - Slamet Riyadi, Bambang (International Journal of Criminology and Sociology, 2022)
This research is a culture of abuse of power due to conflicts of interest so that corruption takes too long to manage oil and natural gas resources in Indonesia in managing oil and natural gas resources in Indonesia. The problem of this research is that the Indonesian state is equipped with abundant natural resources, including oil and natural gas resources. According to Article 33 of the 1945 Constitution, the oil and natural gas resources should be controlled by the state for the greatest prosperity of the people. In fact, the Indonesian people are not prosperous despite the abundance of oil and natural gas resources. Historical research methods. With the concept of cultural criminology. The results of research since the independence of the Republic of Indonesia have occurred abuse of power due to conflicts of interest to maintain power in the management of oil and gas with corruption impacting state losses, especially the suffering of the Indonesian people for too long, so that a culture of corruption is formed. This happens first; the sudden change component, caused by global changes and the modernization of the tendency of society to comply with materialism and consumerism while ignoring the cultural values of shame in the life of the nation and state. that is not trustworthy towards people’s trust. This renewal of research re-shames cultural morality and limits the extent of power that